Risk prediction scoring system to predict the postsurgical outcomes of biliary atresia - Rajeev Redkar; Vinod Raj; Swathi Chigicherla; Shruti Tewari; Chandralekha Tampi; Shirin Joshi (Wolters Kluwer Medknow Publications, 2020)
Aim: To find out association between liver function, liver histopathology and outcomes of biliary atresia (BA) following Kasai Portoenterostomy (KPE). Materials and Methods: This is a retrospective study of children who underwent KPE at a single institute by single surgeon. The patient records analyzed and data of complete blood counts, liver function tests, coagulation profile and histopathology reports collected. The outcomes recorded as alive and jaundice free, alive but jaundiced, and deceased. Statistical analysis done using SPSS 23. Observations: Total of 148 children operated during January 2000 to December 2018. Of these, 26 matched inclusion criteria. The parameters assessed were percentage of direct bilirubin, ratios of Aspartate transaminase (AST) to Alanine transaminase (ALT); Gamma glutamyl transferase (GGT) to AST; GGT to ALT and Aspartate transaminase to platelet ratio index (APRi). Among histopathology reports, fibrosis grade and bile ductular size noted. Among 26, 16 alive and ten are deceased. Among 16 alive, all are jaundice free. Of the parameters, ratio of AST to ALT, APRi and grade of fibrosis found statistically significant and further analysis showed if AST to ALT ratio < 2.1, APRi < 1.8 and grade of fibrosis < four, irrespective of age at surgery, had 96.2 % probability of successful KPE. Based on these observations, a scoring system and risk prediction model constructed based on Receiver operating characteristic (ROC) curves which are first in BA management. Results and Conclusion: Although numbers are sufficient for statistical analysis, we further intend to validate the scoring system in a prospective trial. BA children can be subjected to risk prediction model and KPE performed in those who have a score less than seven and offered to those with score between eight and 16 out of 20. Key Message: The scoring system and risk prediction model can guide in the management and post-operative follow up of children with biliary atresia.